2017
DOI: 10.1016/j.ydbio.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

SHH E176/E177-Zn2+ conformation is required for signaling at endogenous sites

Abstract: Summary Sonic hedgehog (SHH) is a master developmental regulator. In 1995, the SHH crystal structure predicted that SHH-E176 (human)/E177 (mouse) regulates signaling through a Zn2+-dependent mechanism. While Zn2+ is known to be required for SHH protein stability, a regulatory role for SHH-E176 or Zn2+ has not been described. Here, we show that SHH-E176/177 modulates Zn2+-dependent cross-linking in vitro and is required for endogenous signaling, in vivo. While ectopically expressed SHH-E176A is highly active, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Although mutations of the central zinc coordinating triad are unstable and thus cannot be easily assessed for loss of peptidase function, mutations of several other catalytically important residues (E177, H135 and H181) are not destabilized and show a loss in the ability of Shh to enter the ECM. Together with the observation by Himmelstein and colleagues (Himmelstein et al, 2017) that ShhE177A cannot signal from the notochord to the overlying neural plate strongly supports the idea that a Shh-associated peptidase activity is required for non-cell autonomous signaling by promoting its distribution away from the source cells.…”
Section: Are Hhs Proteoglycan Peptidases?supporting
confidence: 64%
See 2 more Smart Citations
“…Although mutations of the central zinc coordinating triad are unstable and thus cannot be easily assessed for loss of peptidase function, mutations of several other catalytically important residues (E177, H135 and H181) are not destabilized and show a loss in the ability of Shh to enter the ECM. Together with the observation by Himmelstein and colleagues (Himmelstein et al, 2017) that ShhE177A cannot signal from the notochord to the overlying neural plate strongly supports the idea that a Shh-associated peptidase activity is required for non-cell autonomous signaling by promoting its distribution away from the source cells.…”
Section: Are Hhs Proteoglycan Peptidases?supporting
confidence: 64%
“…Zinc is a potent agonist of this putative peptidase activity as it increases ECM association of Shh but not of putative peptidase mutants. The observations that Shh-E177A is unable to mediate signaling from the notochord to the overlying neural tube (non-cell autonomously), and is more capable than Shh to induce the Hh response when expressed in the developing neural tube (likely cell-autonomously) (Himmelstein et al, 2017), provides in vivo evidence that the putative zinc-peptidase activity of Shh is required for non-cell autonomous signaling, but not for the activation of the Hh response pe se. The initial experiments that demonstrated that E177 is dispensable for the activation of the Hh response is easily explained as this mutant ligand was added to the responding cells as a purified and soluble fraction (Fuse et al, 1999), thus bypassing the requirement for the peptidase function that we propose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of this mutant in has revealed two interesting properties. First, Shh-E177A is unable to mediate signaling from the notochord to the overlying neural tube (in trans), but is more capable than Shh to induce the Hh response when expressed in the developing neural tube (likely in cis) [28]. Second, purified ShhN-E177A is more stable in solution than ShhN, indicating a cannibalistic peptidase activity that is intrinsic to ShhN.…”
Section: Shh Has All Hallmarks Of a Dd-peptidasementioning
confidence: 99%
“…Published analysis of this mutant has revealed two interesting properties. First, Shh-E177A is unable to mediate Shh signaling from the notochord to the overlying neural tube (in trans), but is more capable than wt Shh to induce the Hh response when expressed in the developing neural tube (likely in cis) (Himmelstein et al, 2017). Second, ShhN-E177A is more stable in solution than ShhN (Rebollido-Rios et al, 2014).…”
Section: The "Pseudo-active" Site Of Shh Has a Role In Shh Function Omentioning
confidence: 99%